2022
DOI: 10.1159/000528086
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor Treatment Has Little Effects on Secretion of Saliva in Patients with Proton Pump Inhibitor-Responsive Mild Reflux Esophagitis and Non-Erosive Reflux Disease

Abstract: <b><i>Introduction:</i></b> The secretion of saliva, which is triggered by acid reflux into the esophagus via the esophagosalivary reflex, plays a crucial role in the defensive mechanisms of the esophagus. The volume of saliva secreted in patients with gastroesophageal reflux disease (GERD) is reduced. However, the effects of proton pump inhibitors (PPI) on the secretion of saliva have rarely been reported. Therefore, the present study investigated changes in the volume and pH of saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…If symptoms worsened, EGD was performed immediately, but this never happened. Since previous studies reported that acid suppressive therapy did not affect saliva secretion, 12 , 13 we performed our study on PPI‐resistant severe RE patients receiving P‐CAB therapy.…”
Section: Methodsmentioning
confidence: 99%
“…If symptoms worsened, EGD was performed immediately, but this never happened. Since previous studies reported that acid suppressive therapy did not affect saliva secretion, 12 , 13 we performed our study on PPI‐resistant severe RE patients receiving P‐CAB therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, 39 patients with NERD (16 males and 23 females), 49 with mild RE (25 males and 24 females), 45 with severe RE (23 males and 22 females), and 46 HCs (24 males and 22 females) were enrolled in this study. Acidsuppressive therapy (PPI or a potassium-competitive acid blocker (PCAB)), which was previously shown to have no effects on saliva secretion [16,17], effectively controlled esophageal mucosal damage and/or reflux symptoms in all GERD patients. HCs, who were consecutively recruited throughout the study period, had an abnormal finding detected during a regular health check-up.…”
Section: Methodsmentioning
confidence: 99%